Numerical simulation of the thermal hydraulic performance of a plate pin fin heat sink - Yuan, Wuhan. (2013)
The computational fluid dynamic software FLUENT is used in assessing the electronics cooling potential of a plate pin fin heat sink (PPFHS), including the conjugate effect. The simulation results are validated with reported experimental data. The simulation shows that pin height and air velocity have significant influences on the thermal hydraulic performances of PPFHS while the influences of in-line/staggered array and neighbor pin flow-directional center distance (NPFDCD) of the PPFHS are less notable. In applying the present design to the cooling of a desktop PC CPU at a heat flux of 2.20 W/cm2, the temperature can be kept at less than 358 K with an air velocity over 6.5 m/s.